How COVID-19 pandemic impacted students’ and staff ’s physical activity at a Brazilian University? - Rafaela Costa Martins; Luiza Isnardi Cardoso Ricardo; Inácio Crochemore-Silva; Flávio Fernando Demarco; Tiago Neuenfeld Munhoz; Mateus Luz Levandowski; Mariana Gonzalez Cademartori; Helena Silveira Schuch; Pedro Curi Hallal (Revista Brasileira de Atividade Física e Saúde)
Introduction: Physical activity and its positive effects on coronavirus have been extensively discussed in the literature. However, there is still a lack of evidence on the effects of the coronavirus pandemic on the health-related behaviors of the Brazilian university community. Objective: To describe physical activity practice during the coronavirus pandemic among students and staff of a southern Brazilian university, as well as its association with sociodemographic characteristics. Methods: This self-administered web-based cross-sectional study was carried out among a southern Brazilian community. The main outcome of this study was leisure time physical activity before and during the coronavirus pandemic. Results: Considering only leisure time, 21% and 24% of the students and staff, respectively, reported achieving physical activity recommendations (≥150 minutes per week). There was a decline of more than 15 percentage points in physical activity practice comparing to pre and during the pandemic, and those following the protocols of staying at home presented lower levels of leisure-time physical activity. Physical activity practice was mainly performed at home and without any professional help. Conclusion: Leisure-time physical activity prevalence during the pandemic was relatively low (compared with Brazilian population) among students and staff, and participants who followed the staying at home protocols presented lower levels of physical activity.